Fullerenes Principles and Applications - Langa De La Puente,Fernando; Nierengarten,Jean-Francois; O'Brien,Paul; Craighead,Harold; Kroto,Harry (Royal Society of Chemistry, The Ingram Publisher Services [Distributor], 2011)
Annotation